1996
DOI: 10.1021/bi961064i
|View full text |Cite
|
Sign up to set email alerts
|

Active Site Structure in Cytochrome c Peroxidase and Myoglobin Mutants:  Effects of Altered Hydrogen Bonding to the Proximal Histidine

Abstract: The globins and peroxidases, while performing completely different chemistry, share features of the iron heme active site: a protoporphyrin IX prosthetic group is linked to the protein by the proximal histidine residue. X-ray absorption spectroscopy provides a method to determine the local structure of iron heme active sites in proteins. Our previous studies using X-ray absorption spectroscopy revealed a significant difference in the Fe-N epsilon bond length between the peroxidases and the globins [for a revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 63 publications
1
23
0
Order By: Relevance
“…However, a similarity in this respect between cytochrome cbb 3 and cytochrome c peroxidase (CcP) is of interest. The catalytic triad in CcP involves a hydrogen bond from the proximal histidine ligand of the protoheme to an aspartate residue (42), and a direct effect of such hydrogen bonding upon the length of the Fe-His bond has been studied in detail (43). EPR experiments of CcP also yielded rhombic heme signals, and mutations of the aspartate led to results very similar to those presented here (42).…”
Section: Thermodynamic Balance In Cytochrome Cbbmentioning
confidence: 54%
“…However, a similarity in this respect between cytochrome cbb 3 and cytochrome c peroxidase (CcP) is of interest. The catalytic triad in CcP involves a hydrogen bond from the proximal histidine ligand of the protoheme to an aspartate residue (42), and a direct effect of such hydrogen bonding upon the length of the Fe-His bond has been studied in detail (43). EPR experiments of CcP also yielded rhombic heme signals, and mutations of the aspartate led to results very similar to those presented here (42).…”
Section: Thermodynamic Balance In Cytochrome Cbbmentioning
confidence: 54%
“…Mb exhibits pseudoperoxidase activity in the presence of H 2 O 2 , catalysing the oxidation of various compounds. Mb pseudoperoxidase activity differs from that of classic peroxidases given the different packing of the haem group within the different protein globules . In particular, myoglobin has low pseudoperoxidase activity, although it is still somewhat considerable because of its higher concentration in skeletal muscles .…”
Section: Resultsmentioning
confidence: 95%
“…Mb pseudoperoxidase activity differs from that of classic peroxidases given the different packing of the haem group within the different protein globules. 27 In particular, myoglobin has low pseudoperoxidase activity, although it is still somewhat considerable because of its higher concentration in skeletal muscles. 9 This activity is of interest in meat conservation because it could influence oxidation in meat systems.…”
Section: Pseudoperoxidase Activity Of Muskox Cattle and Water Buffalmentioning
confidence: 99%
“…Several studies in past years have revealed consistent differences between the structure of the heme in globins and peroxidases [31]. As shown from XAS and high resolution X-ray structures, globins typically have an Fe−N h distance of about 2.1 Å while in the peroxidases this distance is typically shorter by about 0.2 Å, resulting in a typical Fe−N h distance of about 1.9 Å [31][32][33][34][35][36][37][38] (see also Table 3). This was proposed to be crucial to explain the different reactivity observed between the two groups of proteins [34,35].…”
mentioning
confidence: 99%
“…As shown from XAS and high resolution X-ray structures, globins typically have an Fe−N h distance of about 2.1 Å while in the peroxidases this distance is typically shorter by about 0.2 Å, resulting in a typical Fe−N h distance of about 1.9 Å [31][32][33][34][35][36][37][38] (see also Table 3). This was proposed to be crucial to explain the different reactivity observed between the two groups of proteins [34,35]. A significant feature of the peroxidase structures (either Cytochrome C peroxidase, Ccp, or Horseradich peroxidase, Hrp) is the presence of strongly hydrogen-bonding proximal histidine [38].…”
mentioning
confidence: 99%